β-Caryophyllene Ameliorates MSU-Induced Gouty Arthritis and Inflammation Through Inhibiting NLRP3 and NF-κB Signal Pathway: In Silico and In Vivo - Wan-Yang Li; Fan Yang; Ji-Hua Chen; Guo-Feng Ren (Frontiers Media S.A., 2021)
Gouty arthritis serves as an acute reaction initiated by the deposition of monosodium urate (MSU) crystals around the joints. In this study, the anti-inflammatory effects of phytochemical β-caryophyllene on MSU crystal-induced acute gouty arthritis in vivo and in silico were explored. Through bioinformatics methods and molecular docking, it screened the specific influence pathway of β-caryophyllene on gout. Certain methods including enzyme-linked immunosorbent assay, western blotting, and immunohistochemical staining were adopted to quantify. β-caryophyllene significantly reduced inflammation and function of ankle joints in MSU Crystals-induced gouty arthritis rats, while decreasing serum cytokine levels. Furthermore, it inhibited the expressions of NLRP3, Caspase-1, ASC, TLR4, MyD88, p65, and IL-1β in the synovial tissue so as to reduce inflammation and protect ankle joints' function. A new research approach in which β-caryophyllene treatment to acute attacks of gout is provided through the research results.